A molecular-level fire growth parameter. (April 2021) - Lyon, Richard E.; Safronava, Natallia; Crowley, Sean; Walters, Richard N.
Highlights: A simple burning model is used to connect the continuum-level fire response of polymers to molecular-level thermal decomposition kinetics. A micro (10−6 kg) scale fire growth capacity (FGC) is identified that includes ignitability and burning rate, and successfully ranks the performance of 32 polymers in 3 bench scale fire tests. The measurement of FGC using a standard (ASTM D7309-19, Method A) microscale combustion calorimeter is described. ABSTRACT: The relationship between the atomic composition of polymers and the fuel generating reactions in fires has been studied at various levels using molecular dynamics simulations of polymer thermal decomposition, molar group contributions to combustion properties, and finite element models of burning that require properties obtained from thermal analyses. In this study, a conceptual model is used to link the molecular-level processes of flaming combustion measured in thermal analysis to the fire response of a polymer at the continuum level. A scaling parameter emerges from this analysis called the fire growth capacity/ FGC that includes ignitability and burning rate. The FGC was measured in a microscale combustion calorimeter for 32 polymers having a wide range of atomic composition, thermal stability and char forming tendency. It was found that FGC successfully ranks the expected fire performance of these polymers when subjected to a small flame and radiant heat.